Evaluating the investment behavior of community renewable energy project investors and policy recommendations - Ölmez, Eray. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
If countries follow their stated policies it is estimated that there will be no major change in the distribution of energy resources and the share of fossil fuels will remain at a 74% level even in 2040. However, the role of communities and small size investors can play a huge role in the deployment of renewable energy and accordingly contribute to decreasing share of fossil fuels in the distribution of energy sources. This research aims to determine which motivations influence the size of the financial contribution made in community renewable energy projects and factors affecting further investment decisions of the members of the renewable energy cooperatives established in Turkey. In this context, two different frameworks were proposed based on extensive literature review and expert opinions. A questionnaire survey was developed to obtain both qualitative data and quantitative data and directed to members of renewable energy cooperatives established in Turkey. Based on 52 survey answers from 9 different re newable energy cooperatives, the Structural Equation Modeling technique was used for the analysis. The findings of the analysis and successful examples presented in the literature were used to make policy recommendations and to suggest what community renewable energy projects need. The results indicated that (i) household income and importance attached to return on investment are major factors determining the size of investment (ii) new regulation expectation is the major condition precedent for the further investment decision (iii) current policies on renewable energy cooperatives and small size investments need to be developed to increase the deployment of renewable energy and help to meet both national and international goals.
Keywords: Renewable energy.; Fossil fuels.